2014
DOI: 10.2147/ccide.s55761
|View full text |Cite
|
Sign up to set email alerts
|

The effect of xylitol on dental caries and oral flora

Abstract: Dental caries, the most chronic disease affecting mankind, has been in the limelight with regard to its prevention and treatment. Professional clinical management of caries has been very successful in cases of different severities of disease manifestations. However, tertiary management of this disease has been gaining attention, with numerous methods and agents emerging on a daily basis. Higher intake of nutritive sweeteners can result in higher energy intake and lower diet quality and thereby predispose an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 38 publications
2
68
0
4
Order By: Relevance
“…Ksilitol farklı preparatlar ile özellikle yüksek çürük riski bulunan bireylerde, tüketilen karyojenik gıdaların yıkıcı etkisini elimine etmek ve S. mutans sayısını azaltmak amacıyla önerilmektedir. 33 Bu çalışmada, tedavisine değinilen birinci olguda, beyaz nokta lezyonlarının derinliği göz önüne alınarak mikroabrazyon yöntemi ile tedavi gerçekleştirilmiştir. Bu sayede invaziv tedavi seçe-neklerinden kaçınılarak renk stabilitesi sağlanmış-tır.…”
Section: Discussionunclassified
“…Ksilitol farklı preparatlar ile özellikle yüksek çürük riski bulunan bireylerde, tüketilen karyojenik gıdaların yıkıcı etkisini elimine etmek ve S. mutans sayısını azaltmak amacıyla önerilmektedir. 33 Bu çalışmada, tedavisine değinilen birinci olguda, beyaz nokta lezyonlarının derinliği göz önüne alınarak mikroabrazyon yöntemi ile tedavi gerçekleştirilmiştir. Bu sayede invaziv tedavi seçe-neklerinden kaçınılarak renk stabilitesi sağlanmış-tır.…”
Section: Discussionunclassified
“…It has also been found that xylitol causes a disruption of bacterial protein synthesis [2,3,8,9]. No adaptation of the bacteria to a xylitol metabolism was found, even after one year of using the xylitol chewing gum [10].…”
Section: Impact On Bacteria and Plaquementioning
confidence: 99%
“…[10] It is usually found in sugar-free chewing gums, mints, and candies, and even claim that it does not promote tooth decay. [11,12] This is because xylitol, unlike glucose, is not converted into its acidic form, which is the cause of tooth decay, because bacteria in the mouth do not feed on xylitol, which may lead to decreased plaque formation. [11] Although it looks and tastes like table sugar, it has 40% lesser calories because the body cannot fully break down and only absorb 50% of xylitol.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] This is because xylitol, unlike glucose, is not converted into its acidic form, which is the cause of tooth decay, because bacteria in the mouth do not feed on xylitol, which may lead to decreased plaque formation. [11] Although it looks and tastes like table sugar, it has 40% lesser calories because the body cannot fully break down and only absorb 50% of xylitol. [8,9] This means that it intake will not increase the blood sugar and production of insulin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation